The Role of Risk Management Implementation in Increasing Accountability: A Study of All Regency/Municipality Governments - Yudiyanto Yudiyanto; Sri Ningsih (Jurnal Borneo Administrator, 2023)
The regional government is susceptible to risks that may impede attaining objectives while executing its responsibilities and powers, necessitating implementing risk management measures. Implementing risk management in local governments is a novel development, with corresponding guidelines issued in 2019. This study seeks to test whether applying risk management based on these provisions can positively impact increasing financial accountability. The present investigation involves the entirety of the population within the jurisdiction of the regency/municipality government as the research participants. The study's empirical data were acquired from the Financial and Development Supervisory Agency and the Ministry of Administrative and Bureaucratic Reform of the Republic of Indonesia (Kemenpan-RB). Subsequently, the data were subjected to regression analysis techniques utilizing SPSS software. This paper provides findings that entities that implement risk management will have implications for higher SAKIP scores. This implies that risk management can deliver reasonable guarantees to achieving local government goals, especially regarding financial accountability. The present research employs the SAKIP score as a surrogate for assessing accountability, albeit acknowledging its restricted measurement outcomes and partial depiction of local government accountability. Specifically, the SAKIP score delineates the accountability of performance attained by a governmental entity in executing programs and activities funded by the APBN/APBD. The findings of this research possess the potential to be extended to all local governing bodies to enhance the attainment of local government accountability goals.